Algae as potential feedstock for various bioenergy production. (January 2022) - Chia, Shir Reen; Nomanbhay, Saifuddin Bin HJ.M.; Chew, Kit Wayne; Munawaroh, Heli Siti Halimatul; Shamsuddin, Abd Halim; Show, Pau Loke
Abstract: Depletion of non-renewable feedstock and severe wastewater pollution due to human activities have created negative impact to living organisms. The potential solution is to implement wastewater treatment and bioelectricity production through algae-based microbial fuel cell. The algae biomass produced from microbial fuel cell could be further processed to generate biofuels through their unique compositions. The consumption of nutrients in wastewater through algae cultivation and biomass produced to be utilized for energy supply have showed the potential of algae to solve the issues faced nowadays. This review introduces the background of algae and mitigation of wastewater using algae as well as the bioenergy status in Malaysia. The mechanisms of nutrient assimilation such as nitrogen, phosphorus, carbon, and heavy metals are included, followed by the application of algae in microbial fuel cell's chambers. Lastly, the status of algae for bioenergy production are covered. Graphical abstract: Image 1 Highlights: Biofuel is producible using algae from algae bloom and microbial fuel cell (MFC). Algae-based MFCs act as future electricity source and wastewater management system. Bioenergy from algae biomass is potential to replace fossil fuels in future.